Synthesis and characterization of electrospun organic-inorganic hybrid graft copolymer nanofibers of poly(methyl methacrylate) and polydimethylsiloxane - Swart, Morne (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2007.